In search of power and influence: Cronyism and Freemasonry in the Spanish Protectorate of Morocco during the 1920s - Aguiar Bobet, Valeria (Hispania Nova, 2021)
During the 1920s Freemasonry began to gain strength in the Spanish protectorate of Morocco. The debuting lodges will be established in Larache and Alcazarquivir, two of the places furthest from the Riff conflicts and in which the colonial institutions and the Hispanic population were in crescendo and in full socio-economic boom. Our interest lies in analyzing to what extent the components of the Royal Art of both places participated in the same networks, influences, litigation and all kinds of cronyism that characterized the construction and formation of the colonial system, those that would make possible the achievement of the protectorate and the consolidation of certain power groups, especially during the dictatorship of Primo de Rivera. The purpose will be to present a diverse historical landscape, marked and determined by the Freemasons protagonists, by means of different sources produced by Freemasonry, sources that until now have been little used by Spanish historiography.